2020
DOI: 10.24200/amecj.v3.i02.106
|View full text |Cite
|
Sign up to set email alerts
|

A new kinetic models analysis for CO adsorption on palladium zeolite nanostructure by roll-coating technique

Abstract: The aim of this article was the fabrication of Al2O3/Pd(NO3)2/zeolite adsorbent through roll-coating technique for CO gas adsorption. Transmission electron microscopy (TEM), field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and energy-dispersive x-ray spectroscopy (EDX) were performed to investigate the morphological, structural, and elemental properties of Al2O3/Pd(NO3)2/zeolite adsorbent. A continuous gas analyzer KIMO KIGAZ 210 was applied for testing CO gas adsorption on as-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Characterization of the hemp hurds SEM analysis presented in figure 2 illustrates the morphological changes in the unloaded and loaded biosorbent. After the biosorption of heavy metal ions, the surface of the biosorbent became smoother and less porous, suggesting possible physical retention and adsorption of the metal ions onto the biosorbent [37,46]. The surface morphology of the biosorbent is distinctive and rough, providing a favorable environment for adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of the hemp hurds SEM analysis presented in figure 2 illustrates the morphological changes in the unloaded and loaded biosorbent. After the biosorption of heavy metal ions, the surface of the biosorbent became smoother and less porous, suggesting possible physical retention and adsorption of the metal ions onto the biosorbent [37,46]. The surface morphology of the biosorbent is distinctive and rough, providing a favorable environment for adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu(II) ions’ equilibrium concentrations in the solid and liquid phases were expressed using a variety of models, including the Freundlich, Langmuir, Dubinin–Radushkevich (D-R), and Temkin isotherm models (Mozaffari et al 2020a ; Azzam et al 2022 ) These models can be expressed in linearized forms, as demonstrated in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Important derivations from this analysis are as follows: (1) the adsorption of MB on CS-AV follows a FP kinetic model, indicating a deviation from classical first-order kinetics, (2) adsorption rate (𝑘) is relatively high, suggesting a rapid adsorption process and (3) the model moderately fits the experimental data (R 2 values around 0.7). Generally, a value of 𝑣 between 0 and 1 suggests fractional-order kinetics, as obtained in Kuete et al (2020) and Mozaffari et al (2020). The higher the value of 𝑣, the more the kinetics deviate from classical first-order kinetics.…”
Section: B Fractional Power Kinetic Parametersmentioning
confidence: 93%